Efficacy of the Categories of Heirs in Fulfillment of ‘Awl (Increase or Decrease in Inheritance Share); A Comparative Study of the Jurisprudence of Islamic Sects - Muhammad Abu Najmi (مطالعات تطبیقی فقه و اصول مذاهب)
Awl, i.e., reducing the inheritance share (sahm al-’irth) of heirs (wurrāth) and increasing the number of shares to provide the share for all heirs, is a jurisprudential solution for the time that the assets of the deceased (mutiwaffā) is not sufficient for all the shares of heirs and depriving the heirs is also not possible. Some jurists have rejected the ‘awl for its contradiction to jurists’ principles and considered diminishing (naqṣ) in the assets shares of a particular group of sharers as a solution. This research using description and analysis by referring to library sources analyzes the inheritance share of triple categories of brothers and sisters in the Holy Qur’an and concludes that if the stronger category gets priority over the weaker one and it becomes a base for giving shares to heirs, there is no need to refer to awl rule.